Dendrobium officinale polysaccharide ameliorates diabetic hepatic glucose metabolism via glucagon-mediated signaling pathways and modifying liver-glycogen structure. (10th February 2020) - Liu, Yage; Yang, Linlin; Zhang, Yu; Liu, Xiaocui; Wu, Zhijing; Gilbert, Robert G.; Deng, Bin; Wang, Kaiping
Abstract: Ethnopharmacological relevance: Dendrobium officinale polysaccharide (DOP) is the main active ingredient of Dendrobium officinale Kimura & Migo, which is a precious traditional Chinese medicine and often used in treatment of hepatitis, diabetes, obesity and rheumatoid arthritis. Aim of the study : DOP exhibits significant hypoglycemic activity, while its mechanism remains unclear. The present study aims to investigate the hypoglycemic mechanisms of DOP based on the glucagon-mediated signaling pathways and the liver glycogen structure, which catalyze hepatic glucose metabolism, and provide new knowledge about the antidiabetic mechanism of DOP and further evidence for its clinical use for diabetes. Materials and methods: DOP were obtained from the dry stems of Dendrobium officinale by water extraction and alcohol precipitation method. T2DM mice model was established by high-fat diet combined with streptozotocin. Liver histopathological changes were observed by H&E and PAS straining. Pancreatic histology was studied by H&E staining and immunofluorescence analysis. The levels of glucagon and insulin were detected by Elisa Kit and the hepatic glycogen content was detected by GOPOD. The expressions of the hepatic glycogen-related metabolism enzymes, hepatic gluconeogenesis enzymes, and the related protein in cAMP-PKA and Akt/FoxO1 signaling pathways were detected by western blots. Liver glycogen was extracted from the liver tissues by sucrose density gradient centrifugation, and size exclusion chromatography (SEC) was used to analyze the structure of liver glycogen. Results: DOP could significantly affect the glucagon-mediated signaling pathways, cAMP-PKA and Akt/FoxO1, to further promote hepatic glycogen synthesis, inhibit hepatic glycogen degradation and hepatic gluconeogenesis. Moreover, DOP could reverse the instability of the liver glycogen structure and thus probably suppressed glycogen degradation. Thus, DOP finally would ameliorate hepatic glucose metabolism via glucagon-mediated signaling pathways and modifying liver-glycogen structure in diabetic mice. Conclusions: The hypoglycemic mechanism of DOP might be associated with the regulation of glucagon-mediated hepatic glycogen metabolism and gluconeogenesis, and of liver glycogen structure, contributing to improved hepatic glucose metabolism in diabetic mice. Graphical abstract: DOP could regulate glucagon-mediated signaling pathways and reverse the instability of liver glycogen structure, contributing to improved hepatic glucose metabolism. Image 1